Pragmatic Rhetorical Principles in Isocrates - Vidal, Gerardo Ramírez (Peitho. Examina Antiqua, 2017)
While Isocrates regarded rhetoric not as a rigid discipline, but as a creative and pliable art, it is not possible to standardize art. According to his point of view (Against the sophists 13.13), good speech depends on certain principles: opportunity (kairos); suitability (to prepon) and novelty (kainos). The sophists, according to Isocrates, did not pay attention to these principles, and that was their main mistake. The problem was, however, that it was difficult to teach these principles to the disciples, precisely because rhetoric was a flexible art. Still, although it is not possible to provide fixed rules concerning rhetorical principles, the ancient rhetor provided some useful suggestions in his works which make it possible to reconstruct the nature of these principles.